2019
DOI: 10.16949/turkbilmat.495105
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Geometric Habits of Mind and the Mathematics Achievement: The case of Mathematics Preservice Teachers

Abstract: Öz: Geometrik düşünme alışkanlıklarının matematik dersleri üzerindeki etkisini ortaya çıkarmak, kavramsal boyutta öğretimin nasıl gerçekleşeceğine etkileyebilir. Bu kapsamda çalışmanın amacı matematik öğretmeni adaylarının geometrik düşünme alışkanlıkları ile matematik başarıları arasındaki ilişkiyi belirlemektir. Bu amaç doğrultusunda çalışma, bir devlet üniversitesinde matematik öğretmenliği dördüncü sınıfta öğrenim gören 30 öğretmen adayı ile ilişkisel desen yöntemi kullanılarak yürütülmüştür. Çalışmada öğr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…To evaluate the PTs’ progress in geometry and their habits of mind, a GHoM test developed by Bülbül (2016) was implemented before and after the intervention. In addition, at the end of the term, when the treatment ended, the PTs were asked for their views about the implementation process.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To evaluate the PTs’ progress in geometry and their habits of mind, a GHoM test developed by Bülbül (2016) was implemented before and after the intervention. In addition, at the end of the term, when the treatment ended, the PTs were asked for their views about the implementation process.…”
Section: Methodsmentioning
confidence: 99%
“…If a PT drew and explained the new shape, he or she was also considered to apply the habit of exploration and reflection , because an additional drawing was made. Validity and reliability studies of the test, as well as additional test items, can be found in Bülbül (2016).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations